"New terrorism" = higher brutality?: An empirical test of the "brutalization thesis" - Jäckle, Sebastian (Terrorism and political violence, 2017)
This article focuses on the so-called “brutalization” of terrorism. The brutalization thesis as part of the larger theoretical concept of “new terrorism” argues that “new terrorism” is more brutal than “old terrorism.” Many scholars claim that the 9/11 attacks mark the beginning of a new era of terrorism that has lifted international as well as domestic terrorism to a new level of violent brutality. Others argue that this process had already started in the early 1990s. After discussing possible ways to operationalize a brutalization of terrorism, for example focusing on suicide bombings or terrorist attacks against soft targets, this article tests the empirical credibility of the brutalization thesis regarding both potential starting points. Data from the Global Terrorism Database (GTD) shows that only three out of nine indicators increased significantly during the 1990s, partially backing the idea of a general brutalization, whereas increasing numbers of suicide attacks and beheadings after 9/11 support the notion of a qualitative change in terrorism and its brutality connected with the idea of maximizing media and public attention. Yet, these developments are regionally limited and the brutality of this “new terrorism” exceeds the levels known from the zenith of “old terrorism” in the 1970s and 1980s in only a few cases.